Long Way Down : An African Adventure - McGrego, Ewan and Boorman, Charley (London Sphere, 2008)
Longtime friends and bike enthusiasts McGregor and Boorman wowed international audiences with their first major motorcycle journey that spanned several continents, captured in the book and television show Long Way Round. Now they are back, with the fascinating account of their second, equally ambitious journey: from the northernmost tip of Scotland, across Europe and down through Africa ending in Cape Town, this is the account of the authors' three month journey across two continents, over difficult terrain and in unpredictable conditions. Their route covers Britain, Italy, Switzerland, Tunisia, the Sudan, Rwanda, Botswana, and Namibia, among other countries; and they stop in cities and villages along the way to experience the European and African cultures firsthand. Featuring diary entries, travel maps, mileage charts, and dozens of color photographs.--From publisher description.
Include Color Illustration
Keywords: Travel -- McGregor, Ewan, 1971- -- Boorman, Charley -- Africa